2009
DOI: 10.1039/b820818m
|View full text |Cite
|
Sign up to set email alerts
|

Two edge-sharing MnII4MnIII6 supertetrahedra give an anisotropic S = 28 ± 1 MnII6MnIII11 complex

Abstract: A complex with a [Mn(II)(6)Mn(III)(11)] core results via formal fusion of two isotropic Mn(II)(4)Mn(III)(6) supertetrahedra along a common edge leading to a high spin ground state anisotropic system showing Mvs. H hysteresis loops below 1 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
41
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 10 publications
1
41
0
Order By: Relevance
“…Thefit to the thermally activated region above about 0.1 Kgave t 0 = 7 10 À14 sa nd U eff = 19 K. Thes mall value of t 0 ,s maller than is typical for purely SMM behavior,i sa ttributed to the lowlying excited states and the weak intermolecular interactions and is acommon situation for large clusters. [2,22,23,29] At about 0.1 Ka nd below,t he relaxation becomes temperature-independent as expected for relaxation by ground-state QTM, that is,via the M S =AE 61/2 levels of the S = 61/2 spin manifold.…”
Section: Angewandte Chemiementioning
confidence: 64%
See 4 more Smart Citations
“…Thefit to the thermally activated region above about 0.1 Kgave t 0 = 7 10 À14 sa nd U eff = 19 K. Thes mall value of t 0 ,s maller than is typical for purely SMM behavior,i sa ttributed to the lowlying excited states and the weak intermolecular interactions and is acommon situation for large clusters. [2,22,23,29] At about 0.1 Ka nd below,t he relaxation becomes temperature-independent as expected for relaxation by ground-state QTM, that is,via the M S =AE 61/2 levels of the S = 61/2 spin manifold.…”
Section: Angewandte Chemiementioning
confidence: 64%
“…One ideal structural type to act as abuilding block in high nuclearity clusters is the [Mn III 6 Mn II 4 (m 4 -O) 4 ] 18+ supertetrahedral core which combines ab eautiful, high symmetry (T d ) metal topology and interesting magnetic properties. [19] In addition, it has been stabilized in discrete form with several ligands [19][20][21] and under various reaction conditions,a nd has appeared as the repeating unit in zero-dimensional Mn 17 [22,23] and Mn 19 [24] clusters and in the giant Mn 36 Ni 4 "loop-of-loops and supertetrahedra" aggregate, [12] , with that of 1 describing an "A rchimedean solid" called ac uboctahedron. Additionally,t he compounds are structurally related, with the core of 2 being almost identical to afragment of that of 1.Magnetism studies revealed the existence of dominant ferromagnetic exchange interactions in both 1 and 2 leading to ground-state spin values of 61/2 and 51/2, respectively.I na ddition, the magnetocaloric effect for both complexes is seen to develop over as ignificantly wide temperature range.F inally,c ompound 1 displays single-molecule magnet (SMM) behavior and is the second largest homometallic 3d SMM reported to date.…”
mentioning
confidence: 99%
See 3 more Smart Citations